Body condition constrains immune function in field populations of female Australian plague locust Chortoicetes terminifera. (May 2015) - Graham, R. I.; Deacutis, J. M.; Simpson, S. J.; Wilson, K.
Summary The insect innate immune system comprises both humoral and cellular defence responses. In the laboratory, the insect immune system is well characterized. In the field, however, little is known about the role of constitutive insect immune function and how it varies within and between populations. Laboratory studies suggest that host nutrition has significant impact upon insect immune function. Thus, the rationale for this study was to sample natural populations of the Australian Plague Locust Chortoicetes terminifera to establish whether locust body condition (as determined by protein and lipid content) impacted their constitutive immune system and, as a result, has the potential to impact on their capacity to respond to a pathogenic challenge. We found that body condition varied greatly between individual female locusts within sites and that haemolymph protein levels, but not body lipid content, varied between sites. Moreover, our measures of immune function were correlated with the haemolymph levels of protein (in the case of haemocyte density), lipid (prophenoloxidase activity) or both (lysozyme‐like antimicrobial activity). We discuss the implications of these findings for the role of biological pesticides in the control of locust populations.